60 fs, 1030 nm FEL pump–probe laser based on a multi‐pass post‐compressed Yb:YAG source. (14th December 2020) - Viotti, Anne-Lise; Alisauskas, Skirmantas; Bin Wahid, Ammar; Balla, Prannay; Schirmel, Nora; Manschwetus, Bastian; Hartl, Ingmar; Heyl, Christoph M.
Abstract : This paper describes a short‐pulse laser source based on post‐compression via multi‐pass spectral broadening of a 1030 nm burst‐mode laser employed for FEL pump–probe experiments. Abstract : This paper reports on nonlinear spectral broadening of 1.1 ps pulses in a gas‐filled multi‐pass cell to generate sub‐100 fs optical pulses at 1030 nm and 515 nm at pulse energies of 0.8 mJ and 225 µJ, respectively, for pump–probe experiments at the free‐electron laser FLASH. Combining a 100 kHz Yb:YAG laser with 180 W in‐burst average power and a post‐compression platform enables reaching simultaneously high average powers and short pulse durations for high‐repetition‐rate FEL pump–probe experiments.